2019
DOI: 10.1109/access.2019.2958089
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Multi-Message and Multi-Receiver Signcryption Scheme for Heterogeneous Smart Mobile IoT

Abstract: The Internet of Things (IoT) is developing towards smart and mobile Internet of Things (SM-IoT), which has made great progress. Due to the inherent heterogeneity, distribution, intensive communication, and resource constraints of SM-IoT, efficient security and privacy communication protocols become a particularly critical challenge. Signcryption has received considerable attention. Various signcryption schemes have been proposed to solve secure communication. However, most of them are low in efficiency, withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 53 publications
0
31
0
Order By: Relevance
“…The approach finally claims a cost-effective operation considering practical world traces of traffic information. The current study also emphasizes security and interoperable conditions in IoT where signcryption is used for the multireceiver system over the mobile system in IoT (Qiu et al [16).…”
Section: Existing Approachesmentioning
confidence: 99%
“…The approach finally claims a cost-effective operation considering practical world traces of traffic information. The current study also emphasizes security and interoperable conditions in IoT where signcryption is used for the multireceiver system over the mobile system in IoT (Qiu et al [16).…”
Section: Existing Approachesmentioning
confidence: 99%
“…Some MMSC schemes [43]- [49] closely related to this paper are roughly divided into four categories: the PKI-based MMSC schemes [43], [44], the ID-based MMSC scheme [45], the heterogeneous hybrid MMSC schemes [46], [47] and the CL-based MMSC schemes [48], [49].…”
Section: Related Workmentioning
confidence: 99%
“…Therefore, KGC does not have the ability to know the private key of receiver. Qiu et al [47] introduces an efficient secure heterogeneous MMSC scheme for the distributed mobile IoT based on the ID-based cryptography, the CL-based cryptography and ECC. However, the heterogeneous hybrid MMSC schemes [46,47] exist the key escrow issue of the sender in ID-based cryptography and key distribution issue of the receiver in CL-based cryptography.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent times, CL-PKC was studied extensively, since it could conquer certificate management and key escrow problem in the ID-based public-key cryptography. Many certificateless key agreement methods [15-18][20], digital signature techniques without certificate [26][27][28][29], and cryptographic schemes without certificates [30,31][34] [48][49][50][51] have been proposed for various applications. Luo et al [32] projected foremost certificateless on/off-line signcryption (COOSC) scheme [33] [47], demonstrated that it is provably secure in random oracle.…”
Section: Introductionmentioning
confidence: 99%